Double Heterozygosity for Hb Durham-N.C. (HBB: c.344T>C) [β114(G16)Leu→Pro] and the IVS-I-110 (HBB: c.93-21G>A) Causing a Severe β-Thalassemia Phenotype. (4th May 2019) - Cannata, Monica; Cassarà, Filippo; Vinciguerra, Margherita; Licari, Paola; Passarello, Cristina; Leto, Filippo; Lo Pinto, Carmen; Pitrolo, Lorella; Ganci, Riccardo; Maggio, Aurelio; Giambona, Antonino
Abstract: The evaluation of a 10-month-old girl of Sicilian origin with a clinical phenotype of severe thalassemia led to the identification of two β-globin gene defects, a β-thalassemia (β-thal), mutation at IVS-I-110 ( HBB : c.93-21G>A) and a variant hemoglobin (Hb) mutation at codon 114 ( HBB : c.344T>C) on the other allele, reported as Hb Durham-N.C. (also known as Hb Brescia) [β114(G16)Leu→Pro] in the HbVar database. A very low Hb level (Hb 3.5 g/dL), microcytosis [mean corpuscular volume (MCV) 63.2 fL] and hypocromia [mean corpuscular Hb (MCH) 19.6 pg], increased red blood cell (RBC) distribution width (RDW) (36.0%), higher reticulocytes (6.2%), anisocytosis, poikilocytosis, hypocromia, basophilic stippling and inclusion body formation, were present in the affected subject. Analysis of other family components showed the presence of HBB : c.93-21G>A defect in the mother and in her brother, while Hb Durham-N.C. was absent in all other relatives, thus, this mutation has arisen as a de novo defect. This is the first case described as a severe thalassemic phenotype in a compound heterozygote carrier of this unstable Hb and a common β-thalassemic allele. The important information gained from this case is that a rare dominant or recessive mutation may arise in every individual, even if this is a very rare event.